Responsibility For Product Defects In Marketplace Shopee: Study Of Electronic Transactions - Salsabila Athiyyatulmajid; Kuswardhani Kuswardhani; Wardah Yuspin (Publikasi Indonesia, 2023)
Advances in internet technology have given development to buying and selling online. This causes the consumer's position to become weaker in front of the seller because the product to be purchased cannot be checked directly, so if defects are hidden, this can harm consumers. Due to the large number of cases of product defects that occur, this paper will discuss liability for product defects both from the perspective of the electronic transaction information law and according to marketplace policies. According to the ITE Law liability can be in the form of imprisonment and according to the marketplace policy, it will get accumulated penalty points. This study uses normative research methods whereas the data collection technique uses library research. The purpose of this research is so that people who are victims of product defects know what steps to take in seeking accountability according to applicable laws and policies.